Music to Your Brain: Background Music Changes Are Processed First, Reducing Ad Message Recall. Issue 1 (6th December 2012) - Fraser, Cynthia; Bradford, J. Andrew
ABSTRACT Background music captures attention, evokes images, and creates ambience, but may interfere with processing of advertised messages, reducing recall. Brains are hardwired to process unexpected background sound changes first, automatically preempting processing of brand message elements and reducing recall. The degree of this recall reduction depends on the structural characteristics of the music, as well as the advertised brand. Backgrounds with more frequent harmonic and textural changes create more frequent distraction, reducing message recall. Faster tempos increase the frequency of those distractions. However, faster tempos also enable streaming of like distractions, improving message recall. In Experiment 1, backgrounds, varying in harmonic, textural, and temporal characteristics, were compared across ads for six brands. Message recall was higher for ads with backgrounds with less‐frequent change. Message recall from ads for new, unfamiliar brands suffered more from background music interference than from ads for established brands. In Experiment 2, background change frequency was reduced in two ads, holding all else constant, which improved message recall.